Electrolyte and Acid-Base Disorders Triggered by Aminoglycoside or Colistin Therapy: A Systematic Review - Martin Scoglio; Gabriel Bronz; Pietro O. Rinoldi; Pietro B. Faré; Céline Betti; Mario G. Bianchetti; Giacomo D. Simonetti; Viola Gennaro; Samuele Renzi; Sebastiano A. G. Lava; Gregorio P. Milani (MDPI AG, 2021)
Aminoglycoside or colistin therapy may alter the renal tubular function without decreasing the glomerular filtration rate. This association has never been extensively investigated. We conducted a systematic review of the literature following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations. Databases searched included United States National Library of Medicine, Excerpta Medica, and Web of Science. For the final analysis, we evaluated 46 reports, published after 1960, describing 82 cases. A total of 286 electrolyte and acid-base disorders were reported. Hypomagnesemia, hypokalemia, and hypocalcemia were reported in more than three quarter of cases. Further disorders were, in decreasing order of frequency, metabolic alkalosis, hyponatremia, hypophosphatemia, hypouricemia, hypernatremia, and metabolic acidosis. Six electrolyte and acid-base disorders were reported in seven cases, five in 12 cases, four in 16 cases, three in 31 cases, two in 11 cases, and one in five cases. Laboratory features consistent with a loop of Henle/distal tubular dysfunction were noted in 56 (68%), with a proximal tubular dysfunction in three (3.7%), and with a mixed dysfunction in five (6.1%) cases. The laboratory abnormality was unclassified in the remaining 18 (22%) cases. Treatment with aminoglycosides or colistin may trigger a proximal tubular or, more frequently, a loop of Henle/distal tubular dysfunction.